Ответ:
-2/3
Пошаговое объяснение:
(-2/3 + 5/12) + (-0,45) + (-5/12 + 9/20) =
-2/3 + 5/12 - 0,45 - 5/12 + 9/20 =
-2/3 + 5/12 - 9/20 - 5/12 + 9/20 =
-2/3 + (5/12 - 5/12) + (-9/20 + 9/20) =
-2/3 + 0 + 0 = -2/3
ответ:-2/3...........
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
-2/3
Пошаговое объяснение:
(-2/3 + 5/12) + (-0,45) + (-5/12 + 9/20) =
-2/3 + 5/12 - 0,45 - 5/12 + 9/20 =
-2/3 + 5/12 - 9/20 - 5/12 + 9/20 =
-2/3 + (5/12 - 5/12) + (-9/20 + 9/20) =
-2/3 + 0 + 0 = -2/3
Ответ:
ответ:-2/3...........